A Responsive Web-Based Information System to Support Digital School Management and Educational Information Services - Andreas Andoyo; Agus Suryana; Yoga Kusuma; Rahmat Hidayat (YHMM PUBLISHING, 2026)
Digital transformation has encouraged educational institutions to adopt web-based information systems to improve information services and communication quality. This study aims to design and implement a web-based information system for MTs Nurul Huda Pugung, Tanggamus, as an integrated platform for school information dissemination and promotion. The research employed the Waterfall software development model, including requirements analysis, system design, implementation, testing, and maintenance. The system was developed using responsive web technology to ensure accessibility across desktop and mobile devices. System evaluation involved 31 respondents, consisting of 8 teachers and 23 eighth- and ninth-grade students, using a Likert-scale questionnaire. The evaluation results indicated user satisfaction scores of 90.6% for user interface design, 92.4% for usability, and 91.8% for system effectiveness, resulting in an overall satisfaction score of 91.6%, categorized as excellent. These findings demonstrate that the proposed system effectively improves information accessibility, accelerates school information dissemination, and supports the digital transformation of educational services. The proposed model can serve as a practical reference for implementing web-based information systems in schools with similar organizational characteristics.